Tissue distribution of the Ehrlichia muris-like agent in a tick vector. - Geoffrey E Lynn; Jonathan D Oliver; Curtis M Nelson; Roderick F Felsheim; Timothy J Kurtti; Ulrike G Munderloh (PLoS ONE, 2015)
Human pathogens transmitted by ticks undergo complex life cycles alternating between the arthropod vector and a mammalian host. While the latter has been investigated to a greater extent, examination of the biological interactions between microbes and the ticks that carry them presents an equally important opportunity for disruption of the disease cycle. In this study, we used in situ hybridization to demonstrate infection by the Ehrlichia muris-like organism, a newly recognized human pathogen, of Ixodes scapularis ticks, a primary vector for several important human disease agents. This allowed us to assess whole sectioned ticks for the patterns of tissue invasion, and demonstrate generalized dissemination of ehrlichiae in a variety of cell types and organs within ticks infected naturally via blood feeding. Electron microscopy was used to confirm these results. Here we describe a strong ehrlichial affinity for epithelial cells, neuronal cells of the synganglion, salivary glands, and male accessory glands.